Dielectric flow observation at inter-electrode gap in micro-electro-discharge-milling process. (May 2018) - Mullya, SA; Karthikeyan, G
The material removal phenomenon of sparking and melting in micro-electro-discharge-milling process occurs at inter-electrode gap of dimension less than 50 µm. The behavior of fluid flow properties at inter-electrode gap is not well discussed in the literature and its information will be useful to understand the material flow behavior and tool wear in micro-electro-discharge-milling process. Based on our previous findings, it was well recognized that tool rotation is an inherent part of micro-electro-discharge-milling and directly influences debris flushing and redeposition. Also for a stable machining performance, flow of dielectric will play an important role in flushing away debris from the gap. The objective of this work is to investigate the fluid flow along the inter-electrode gap and to study its effect on debris movement and molten metal redeposition. The fluid flow along the narrow gap of micro-electro-discharge-milling process for different machining conditions is analyzed by computational fluid dynamics simulation. By particle simulation, the effect of different sized particles formed at various positions and their subsequent movement was also analyzed. The computational fluid dynamics analysis results were validated with scanning electron micrographs obtained for various machining conditions of the experiments. The effect of inlet nozzle velocity, tool rotation and size of electrode gap on the dielectric fluid flow was primarily reported and the findings were later superimposed on particle injection velocity to determine the movement of debris along inter-electrode gap. The effect of debris movement on redeposition at workpiece/tool surface and its ejection from inter-electrode gap is recounted.